KEMAMPUAN KONSUMSI RUMAH TANGGA, INVESTASI DAN PENGELUARAN PEMERINTAH DALAM MENJELASKAN INDEKS PEMBANGUNAN MANUSIA (IPM) DI KALIMANTAN BARAT - B61112037, Helmi Noviansyah (Jurnal Ekonomi Daerah (JEDA), 2019)
The purpose of this study was to determine and analyze the influence of household consumption, investment, and government expenditure on the Human Development Index (HDI) in West Kalimantan. Object of research include 14 Regency/Town in West Kalimantan with the data source used is secondary data obtained from GRDP Expenditure 2012-2016 and data on HDI 2012-2016 published by the Statistics Indonesia (BPS). The Instrument of this research was the analysis of data panel regression. The result of this research showed that Household Consumption and Government Expenditure influence significantly to Human Development Index (HDI) in West Kalimantan, while Investment has not influence significantly to HDI in West Kalimantan.Keywords: Household Consumption, Investment, Government Expenditure and Human Development Index (HDI).